PENGARUH IMPLEMENTASI SISTEM INFORMASI MANAJEMEN ZAKAT BAZNAS (SIMBA) TERHADAP PENGELOLAAN ZAKAT KOTA BOGOR: SIMBA Pengelolaan, Pengumpulan, Pendistribusian Zakat, BAZNAS Kota Bogor - witri Aulia maudy; Kholil Nawawi (Ekonomi Islam, 2019)
This study aims to determine implementation of the zakat management system, otherwise known as SIMBA and the influence of SIMBA towards the management of zakat in the form of collection and distribution zakat. The methodology in this study uses a simple linear regression method with SPSS tools. Based on the results of the study that the implementation of SIMBA in BAZNAS Bogor city has not been fully implemented seen in the results of research output with SPSS it is known that SIMBA implementation has an effect of 20.4% and distribution of 27.8%.